Agronomic performance, phytochemical profile, and preliminary anti-mold potential of Marigold (Tagetes spp.) in semi-arid ecosystems - CATOOTJIE L. NALLE; I KOMANG SUDARMA; STORMY VERTYGO; ERDA E. RAME HAU; DINA V. SINLAE (Society for Indonesian Biodiversity, 2026)
Abstract. Nalle CL, Sudarma IK, Vertygo S, Hau EER, Sinlae DV. 2026. Agronomic performance, phytochemical profile, and preliminary anti-mold potential of Marigold (Tagetes spp.) in semi-arid ecosystems. Biodiversitas 27 (7): d270725. https://doi.org/10.13057/biodiv/d270725. Marigold is a bioactive-rich plant with potential in animal nutrition; however, studies in semi-arid environments remain limited, restricting understanding of its agronomic and phytochemical variability. This study evaluated the agronomic performance and phytochemical composition of several marigold varieties and explored their potential as feed additives based on phytochemical characteristics and preliminary antifungal activity. Seven marigold varieties (Casanova, Kasuari, Maharani, Diwali, Beautiful 008, Garuda, and Nirwa) were evaluated using a randomized complete block design with seven treatments and four blocks (420 plants). Seedlings were transplanted at 14 days and cultivated under standard agronomic practices. Growth, morphological traits, flower yield, and bioactive compounds were determined using High-Performance Liquid Chromatography (HPLC) and spectrophotometry. Antifungal activity of Maharani and Diwali extracts against Aspergillus flavus was assessed by agar disk diffusion, and their ground flowers were applied to naturally contaminated stored corn in a randomized complete design (three treatments, six replicates). Grain physical quality and total aflatoxin content were evaluated. Significant varietal differences (P<0.05-0.01) were observed in agronomic and phytochemical traits. Maharani produced the highest flower number (97.5 flowers) and fresh flower yield (1404.5 g). Although marigold application did not significantly affect (P>0.05) grain physical quality or aflatoxin concentration, Maharani extract showed strong antifungal activity, producing an inhibition zone of 21.2 mm. Garuda exhibited the highest carotenoid and flavonoid contents, whereas Diwali contained the highest phenolic concentration with favorable agronomic performance. These findings demonstrate varietal complementarity and support the selection of specific marigold genotypes for dual-purpose use in biomass production and bioactive applications for animal feed.